Hubungan Antara Komunikasi Kelompok Guru dengan Motivasi Belajar Murid pada Masa PTMT - Azhar Panji Pratama; Anne Maryani (Bandung Conference Series: Communication Management, 2023)
Abstract. The Covid 19 outbreak has enveloped Indonesia since 2020, of course this has an impact on all aspects of life in Indonesia, especially in the education aspect. Face-to-face education must now be replaced by online learning since PPKM was implemented. This policy reduces students' learning motivation because they are not familiar with the online learning process. Since the COVID-19 pandemic has begun to subside, the government has implemented a PTMT policy or Limited Face-to-face Learning at the SMA/SMK equivalent education level. As a communicator in the communication process that occurs in learning at school, a teacher must convey messages properly to the communicant or his students. The PTMT policy makes the distribution of material provided by the teacher less evenly distributed, because this policy is a hybrid which makes students divided into two groups, some are learning face-to-face and some are learning online. This makes the teacher have to conduct group discussions to find solutions to these problems. The research entitled "The Relationship Between Teacher Group Communication With Student Learning Motivation During the Ptmt Period (Limited Face-to-Face Learning)", has a problem statement whether there is a relationship between teacher group communication and student learning motivation during the PTMT period. This study aims to determine the relationship between teacher group communication and student learning motivation during the PTMT (Limited Face-to-face Learning) period and to examine the psychodynamic theory of group function. In determining the respondents to be studied, researchers used simple random sampling with the results of PFPT teachers and level 3 PFPT students at SMKN 1 Cimahi who would be respondents in this study. This study uses quantitative methods with data collection techniques using questionnaires as primary data and interviews as secondary data. Data analysis will be carried out using the correlational study method and calculated using the SPSS application. The results showed that there was a significant relationship between teacher group communication and student learning motivation during the PTMT period. The relationship between the two variables has a fairly strong strength with a positive relationship direction. Abstrak. Wabah Covid 19 menyelimuti Indonesia sejak tahun 2020, tentunya hal ini berdampak kepada semua aspek kehidupan yang ada di Indonesia terutama pada aspek pendidikan. Pendidikan tatap muka secara langsung kini harus diganti oleh pembelajaran secara daring sejak PPKM dilakukan. Kebijakan ini membuat motivasi belajar murid menurun karena belum terbiasa dengan proses pembelajaran daring. Sejak pandemi covid-19 sudah mulai mereda, pemerintah melakukan kebijakan PTMT atau Pembelajaran Tatap Muka Terbatas pada jenjang pendidikan SMA/SMK sederajat. Sebagai komunikator dalam proses komunikasi yang terjadi pada pembelajaran di sekolah, seorang guru harus menyampaikan pesan dengan baik kepada komunikan atau murid-muridnya. Kebijakan PTMT membuat pembagian materi yang diberikan guru kurang merata, karena kebijakan ini bersifat hybrid yang membuat siswa siswi terbagi menjadi dua kelompok, ada yang belajar tatap muka dan ada yang belajar daring. Hal ini membuat guru harus melakukan diskusi kelompok untuk mencari solusi dari masalah tersebut. Penelitian yang dibuat dengan judul “Hubungan Antara Komunikasi Kelompok Guru Dengan Motivasi Belajar Murid Pada Masa Ptmt (Pembelajaran Tatap Muka Terbatas)”, memiliki rumusan masalah apakah terdapat hubungan antara komunikasi kelompok guru dengan motivasi belajar murid pada masa PTMT. Penelitian ini memiliki tujuan untuk mengetahui hubungan antara komunikasi kelompok guru dengan motivasi belajar murid pada masa PTMT(Pembelajaran Tatap Muka Terbatas) dan menguji teori psikodinamika dari fungsi kelompok. Dalam menentukan responden yang akan diteliti, peneliti menggunakan simple random sampling dengan hasil guru PFPT dan murid tingkat 3 PFPT SMKN 1 Cimahi yang akan dijadikan responden dalam penelitian ini. Penelitian ini menggunakan meotde kuantitatif dengan teknik pengumpulan data menggunakan kuesioner sebagai data primer dan wawancara sebagai data sekunder. Data analisa yang akan dilakukan dengan menggunakan metode studi korelasional dan dihitung menggunakan aplikasi SPSS. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara komunikasi kelompok guru dengan motivasi belajar murid pada masa PTMT. Hubungan antara kedua variabel tersebut memiliki kekuatan yang cukup kuat dengan arah hubungan positif.